ANALISIS GREEN PRODUK, GREEN MARKETING DAN GREEN KNOWLADGE DI KOTA SEMARANG - Rahmi Yuliana; Setyo Pantawis (ITB AAS INDONESIA Surakarta, 2022)
This study aims to analyze how big the consumer's decision in using The Body Shop product in the city of Semarang. The sample used in this study was 100 people using the accidental sampling method, namely the method in selecting the sample. In this study, purchasing decisions were significantly influenced by green product, purchasing decisions are significantly influenced by Green Marketing, purchasing decisions are significantly influenced by Green Knowledge. Keywords: Green product, Green Marketing, Green Knowledge